1999
DOI: 10.1021/cm980741n
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous WO3 Films via Chemical Vapor Deposition from Metallorganic Precursors Containing Phosphorus Dopant

Abstract: Amorphous WO3 films, doped with phosphorus, have been synthesized by chemical vapor deposition of volatile, low-melting P-substituted tungsten carbonyls. The presence of a small quantity of dopant released by the precursor during its decomposition is sufficient to inhibit the crystallization of the tungsten oxide on the matrix (P/W 2−4 atom % on Si(100) and ca. 10 atom % on KGlass). The nature of the film is scarcely affected by the experimental conditions of deposition (namely p O 2 partial pressure) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
0
10
1
Order By: Relevance
“…940 cm ±1 , and becomes slightly sharper after thermal treatment of the films. In contrast to analogous spectra obtained from polycrystalline samples grown from W(CO) 6 , [10] all the samples appear to be amorphous, irrespective of the temperature of the post- deposition treatment. This fact is confirmed by diffractometric analysis.…”
Section: Deposition On Kglasscontrasting
confidence: 60%
See 1 more Smart Citation
“…940 cm ±1 , and becomes slightly sharper after thermal treatment of the films. In contrast to analogous spectra obtained from polycrystalline samples grown from W(CO) 6 , [10] all the samples appear to be amorphous, irrespective of the temperature of the post- deposition treatment. This fact is confirmed by diffractometric analysis.…”
Section: Deposition On Kglasscontrasting
confidence: 60%
“…[9] We have recently reported that good quality amorphous WO 3 films can be obtained by CVD from metal±organic precursors containing a phosphorous dopant, such as W 2 -(l-PR 2 ) 2 (CO) 8 (R = Me, Et), trans-and cis-W(CO) 4 -(PEt 3 ) 2 , and trans-W(CO) 4 [P(OEt) 3 ] 2 . [10] In that case it was possible to grow amorphous films at high temperatures by taking advantage of the ability of oxidized phosphorous derivatives to vitrify the host matrix. [11] In this paper, we suggest an alternative synthetic route using an oxoalkoxide of W VI (the tetra-tert-butoxide derivative WO(O t Bu) 4 ) as the CVD precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nanoparticulate or nanoporous films are usually desired. Normally, the approaches for producing large surface area electrodes include sol–gel deposition,7 sintering nanoparticles,8 chemical vapor deposition9 and electrodeposition 10. Among various methods for the synthesis of nano‐structures, the fabrication of self‐organized oxide nanotube (NT) arrays by a simple but optimized electrochemical anodization of a metal substrate represents a most elegant and economic approach 11.…”
Section: Introductionmentioning
confidence: 99%
“…Thin films and nanostructures of tungsten oxides have been fabricated by thermal evaporation [6], vapor-solid growth [7], chemical vapor deposition [8], hydrothermal synthesis [9], sol-gel process [10], solvothermal process [11], electrodeposition [12], and electrochemical anodization [13]. Recently, the anodization process using an anodic aluminum oxide (AAO) mask was used to produce tungsten oxide nanorods with good vertical alignment on a substrate [14].…”
Section: Introductionmentioning
confidence: 99%